Peningkatan Hasil Belajar Siswa dengan Menerapkan Video Identifikasi Campuran Kopi Menggunakan Metode Spektroskopi UV-Visible - Ummu Aiman; Nirwana Nirwana; M Lutfi Firdaus (PendIPA Journal of Science Education, 2019)
Abstract[Improvement of students learning outcomes by applying the video of coffee-mixture identification using UV-Visible Spectroscopy]. The purpose of this study was to evaluate the differences of student learning outcomes on electromagnetic wave materials and how students respond to the learning videos. This research was an experimental research which applies video coffee-mixture identification. The study was conducted in grade X islamic high school consisting of experimental class and control class. Based on the data analysis, the average post-test grade of the experimental class was 82.11 and the mean post-test control grade was 72.88 with tcount = 0,038 which is lower than the value of significance (0,05). The N-gain values of both classes indicate that the experimental class (0.72) is better than the control class (0.61). This suggests the adoption of a coffee-mixture identification video on electromagnetic wave material able to improve greater learning outcomes than control class that did not apply the video to the learning process. The result of questionnaire analysis shows that the student response to video implementation is good, as seen from the average score of responses of students who answered strongly agree at 40% level, while the answer agree at 53.83% level, not agree at 5.43% level and who answered very disagreeing 0.74% of all students. Keywords: Coffee-mixture; UV-Visible spectroscopy; electromagnetic waves; learning video.(Received August 15 2018; Accepted January 25, 2019; Published February 25, 2019) AbstrakPenelitian ini dilakukan dengan tujuan untuk menjelaskan perbedaan peningkatan hasil belajar siswa pada materi gelombang elektromagnetik dan bagaimana respon siswa terhadap video pembelajaran. Penelitian ini merupakan penelitian eksperimen yang menerapkan video identifikasi campuran kopi. Penelitian dilaksanakan di Madrasah Aliyah kelas X yang terdiri dari kelas eksperimen dan kelas kontrol. Berdasarkan hasil analisis data, rata-rata nilai post-test kelas eksperimen adalah 82,11 dan rata-rata nilai post-test kelas kontrol 72,88 dengan nilai thitung = 0,038 < nilai signifikansi (0,05). Adapun nilai N-gain dari kedua kelas menunjukkan bahwa pada kelas eksperimen  (0,72) lebih baik dari  pada kelas kontrol (0,61). Hal ini menunjukkan bahwa penerapan video identifikasi campuran kopi pada materi gelombang elektromagnetik dapat meningkatkan hasil belajar yang lebih besar dibandingkan kelas kontrol yang tidak menerapkan video pada proses pembelajarannya. Sedangkan hasil analisis angket diketahui bahwa respon siswa terhadap penerapan video adalah baik, terlihat dari nilai rata-rata respon siswa yang menjawab sangat setuju sebesar 40%, sedangkan yang menjawab setuju sebesar 53,83%, tidak setuju sebesar 5,43% dan  yang menjawab sangat tidak setuju sebesar 0,74% dari keseluruhan siswa. Kata kunci: Campuran kopi; spektroskopi UV-Vis; gelombang elekromagnetik; video pembelajaran